METHOD AND SYSTEM FOR AUTOMATED INTERPRETATION OF COMPUTER TOMOGRAPHY SCAN DATA (2009)
Disclosed is a method for interpreting image data that represents variations in density of matter inside a subject. For instance, a data processing system may receive image data from a scan of a subject. The data processing system automatically discerns one or more bones, one or more arteries, and one or more organs of the subject, based at least in part on the image data. The data processing system may also automatically identify one or more of the discerned bones, arteries, and organs. The data processing system may also produce output that depicts one or more of the identified bones, one or more of the identified arteries, and/or one or more of the identified organs, for use by a radiologist or other user. Other embodiments are described and claimed.